Digital Behavior: How Cognition Social Forming Behavior Consumers in Today's Era - Ian Zulfikar (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
In the digital era, understanding consumer behavior is very important for business success. This is in a way to directly influence decisions, starting from determining organizational objectives to marketing strategies. Research This aims to analyze How social cognition- as a mental process that involves perception, interpretation and understanding to other people's behavior- can give impact to the behavior of Consumers in the Digital Age. This research uses a qualitative approach with descriptive method. Research results show that social cognition plays an important role in forming consumer behavior through social media influence, online reviews, and recommendations. Third factor This creates social interaction, trust, and influences collective influence consumer purchase intention in the digital age. Consumers are now more critical and selective, so that companies need to adjust their marketing strategy to their pattern of thoughts and needs. Four key strategies — consistent digital presence, experience delighted customers, relevant personalization, and utilization data analytics — be key for building credibility, increasing loyalty, and maintaining the company's Competitive Power.